Analisis risiko imbal hasil pembiayaan perbankan syariah ‎di era new normal - Rohimah, Wasilatur (Maliki Interdisciplinary Journal, 2023)
This study aims to determine the returns on sharia banking financing in the new new normal era. This study uses a qualitative descriptive research method with a Literature Review approach. By analyzing the risk of returns on financing in Islamic banking in the new normal era, this research will produce a description or picture. This study uses secondary data, namely monthly serial data obtained from the official websites of the Financial Services Authority (OJK) and Bank Indonesia (BI) to obtain information about the financing to be studied, namely murabahah, mudharabah and istishna financing. The data used is Outstanding and Rate of return data types. The results of the study show that the new normal era has also had a good impact on economic development, this is shown by the assets of Islamic banking and Islamic business units (UUS) which have increased until 2021, Islamic banking assets are 441,789 billion Rupiah while Islamic Business Unit assets (UUS) are 234,947 Billion Rupiah, this amount is quite a large amount compared to the amount in the previous year, especially in the year of the economic crisis caused by the co-19 pandemic.